Antiangiogenic potential of Elaeagnus umbellata extracts and molecular docking study by targeting VEGFR-2 pathway - Nazir Nausheen; Waqar Arbaz; Zaib Khan Amir; Ali Khan Ayaz; Aziz Tariq; Alasmari Abdullah F. (Open Medicine)
Anti-angiogenesis or inhibition of blood vessel formation is the best way to prevent the growth and metastasis of tumors. Natural sources like plants are currently being explored for its antiangiogenic activity as they are factories of various phytochemicals. The goal of the current study is to investigate the antiangiogenic potential of Elaeagnus umbellata (E. umbellata) by using chorioallantoic membrane (CAM) assay and molecular docking.